Practical one-pot stereospecific preparation of vicinal and 1, 3-diols. Issue 1 (4th January 2017) - Bohman, Bjorn; Flematti, Gavin R.; Unelius, C. Rikard
Graphical abstract: Highlights: One-pot facile synthesis of bioactive diols. All possible stereoisomers can be prepared in high purity. Commercially available starting materials are used. Important route to cyclic acetal pheromones. Abstract: A facile one-pot synthesis providing vicinal diols and 1, 3-diols in >95% stereoisomeric purity from commercially available enantiopure hydroxy esters has been developed. The esters were reduced with DIBALH and alkylated in situ with 4-pentenylmagnesium bromide, which after workup generated the title diols as diastereomeric pairs. These pairs were easily separated by preparative chromatography, affording products with retained stereoisomeric purity from the starting materials. This method represents an expedient preparation of many common natural products, such as cerambycid beetle pheromones and intermediates towards bicyclic acetal bark beetle pheromones.